2016
DOI: 10.5370/jeet.2016.11.3.733
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Simulation of Modifiable Bipedal Walking on Uneven Terrain with Unknown Height

Abstract: -To achieve bipedal walking in real human environments, a bipedal robot should be capable of modifiable walking both on uneven terrain with different heights and on flat terrain. In this paper, a novel walking pattern generator based on a 3-D linear inverted pendulum model (LIPM) is proposed to achieve this objective. By adopting a zero moment point (ZMP) variation scheme in real time, it is possible to change the center-of-mass (COM) position and the velocity of the 3-D LIPM throughout the single support phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Nevertheless, the biped robot will not lose its stability if the ZMP exceeds the stable region in a very short time. This situation can also be seen in other references, such as [35][36][37]. From Figure 22, it is observed that the biped can walk stably with no sliding.…”
Section: Walking On Uneven Groundsupporting
confidence: 74%
“…Nevertheless, the biped robot will not lose its stability if the ZMP exceeds the stable region in a very short time. This situation can also be seen in other references, such as [35][36][37]. From Figure 22, it is observed that the biped can walk stably with no sliding.…”
Section: Walking On Uneven Groundsupporting
confidence: 74%